Supercooled Southern Ocean Waters. Issue 20 (22nd October 2020) - Haumann, F. Alexander; Moorman, Ruth; Riser, Stephen C.; Smedsrud, Lars H.; Maksym, Ted; Wong, Annie P. S.; Wilson, Earle A.; Drucker, Robert; Talley, Lynne D.; Johnson, Kenneth S.; Key, Robert M.; Sarmiento, Jorge L.
Abstract: In cold polar waters, temperatures sometimes drop below the freezing point, a process referred to as supercooling. However, observational challenges in polar regions limit our understanding of the spatial and temporal extent of this phenomenon. We here provide observational evidence that supercooled waters are much more widespread in the seasonally ice‐covered Southern Ocean than previously reported. In 5.8% of all analyzed hydrographic profiles south of 55°S, we find temperatures below the surface freezing point ("potential" supercooling), and half of these have temperatures below the local freezing point ("in situ" supercooling). Their occurrence doubles when neglecting measurement uncertainties. We attribute deep coastal‐ocean supercooling to melting of Antarctic ice shelves and surface‐induced supercooling in the seasonal sea‐ice region to wintertime sea‐ice formation. The latter supercooling type can extend down to the permanent pycnocline due to convective sinking plumes—an important mechanism for vertical tracer transport and water‐mass structure in the polar ocean. Plain Language Summary: Ocean water, which contains about 34 grams of salt per kilogram of seawater, generally freezes around −1.85°C. However, seawater can be cooled to even lower temperatures without turning into ice. This phenomenon is called supercooling. Supercooled water is found in the polar oceans, typically in regions where the ocean is in contact with ice, as is the case for the enormous seasonal sea‐ice region around Antarctica. But collecting measurements in this region under the thick ice cover during the dark and cold Antarctic winter is challenging. Here, we supplement rather sparse traditional ship‐based observations with data collected by autonomous floats and instrumented marine mammals to detect and analyze where, when, and how supercooled seawater forms in the Southern Ocean. We find widespread supercooling related to melting floating glaciers (ice shelves) along the Antarctic coast and sea‐ice formation. Our analysis enables us to detect sinking supercooled plumes from sea‐ice formation, which may be important for cooling the deep ocean and transporting constituents such as carbon, nutrients, or oxygen from the ocean's surface to deeper layers. Key Points: Potential and in situ supercooling occurs in large parts of the Southern Ocean seasonal sea‐ice zone Deep coastal supercooling from below 100 m to the ocean bottom is associated with melting ice shelves and dense shelf water formation Shallow supercooling is associated with sea‐ice formation and can penetrate as deep as the permanent pycnocline